Sonicated Sol-gel Preparation of Nanoparticulate ZnO Thin Films with Various Deposition Speeds: The highly Preferred c-axis (0 0 2) Orientation Enhances the Final Properties - Ayib Rosdi, Zainun; M. F., Malek; Mohd Hafizan, Mamat; Z., Khusaimi; M. Z., Sahdan; M. Z., Musa; A. B., Suriani; N. D., Md Sin; S. B., Abd Hamid; M., Rusop (Elsevier Ltd, 2014)
Zinc oxide (ZnO) thin films have been deposited onto glass substrates at various deposition speeds by a sonicated sol-gel dip-coating technique. This work studies the effects of deposition speed on the crystallisation behaviour and optical and electrical properties of the resulting films. X-ray diffraction (XRD) analysis showed that thin films were preferentially oriented along the (0 0 2) c-axis direction of the crystal. The transformation sequence of strain and stress effects in ZnO thin films has also been studied. The films deposited at a low deposition speed exhibited a large compressive stress of 0.78 GPa, which decreased to 0.43 GPa as the deposition speed increased to 40 mm/min. Interestingly, the enhancement in the crystallinity of these films led to a significant reduction in compressive stress. All films exhibited an average transmittance of greater than 90% in the visible region, with absorption edges at ∼380 nm. The photoluminescence (PL) measurements indicated that the intensity of the emission peaks varied significantly with deposition speed. The optical band gap energy (Eg) was evaluated as 3.276–3.289 eV, which increased with decreasing compressive stress along the c-axis. The energy band gap of the resulting ZnO films was found to be strongly influenced by the preferred c-axis (0 0 2) orientation.